Professional Skepticism as an Intervening Variable in the Relationship Between Auditor Competence, Time Budget Pressure and Forensic Expertise with the Auditor's Ability to Detect Fraud - Gusti Ayu Dewi Anggreni; Edy Sujana; I Putu Gede Diatmika (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Study This aim for analyze influence auditor competence, time budget pressure and expertise forensics to auditor's ability in detect cheating, with skepticism professional as intervening variables. Background study This based on the number of case fraud in report finances that are not detected by auditors, as happened at PT Asuransi Adisarana Wanaartha Life, NMC Health, as well various case abuse financial situation in the Village Credit Institution (LPD) environment in Bali, shows existence weakness in function auditor supervision. This cause question critical about factors that influence auditor effectiveness in identify fraudulent actions. Study This use approach quantitative with type study associative causal. Sample in study This is all auditors at 20 Public Accounting Firms in the Bali region, totaling 136 respondents, were determined through technique sample saturated. Data collected use questionnaire and analyzed with technique SEM-PLS statistics. Variables free in study This consists of from auditor competence, pressure budget time (time budget pressure) and expertise forensics; variables mediation is skepticism professional and variables dependent is auditor's ability in detect cheating. Research result show that auditor competency and expertise forensics own influence positive and significant to auditor's ability in detect cheating. On the contrary, pressure budget time own influence negative to ability In addition, skepticism​ professional proven capable mediate influence competence, pressure time and expertise forensics to ability detect fraud. This means that the higher the professional auditors’ skepticism, increasingly big his abilities in disclose cheating, even though confronted with limitations audit time and complexity. Findings This give contribution theoretical in development of auditor behavior models based on theory attribution and theory dissonance cognitive. In terms of practical, results study This can become input important for Public Accounting Firms in increase audit quality with notice aspect competence, management pressure time and training skill forensics to grow attitude skeptical high professionalism​ in auditor self. With Thus, it is hoped the role of the auditor as guard reliability report finance can walk more optimal.